Scale Dependent Relationships Between Precipitation and Atmospheric Source Nitrate: Insights From the Yarlung Tsangpo River Basin - Feng Wang; Yongqin Liu; Dongmei Qu; Yunting Fang; Anyi Hu; Yueang Li; Zhihao Zhang; Bin Zhang; Junzhi Liu (Geophysical Research Letters, 2025)
Abstract Precipitation can increase the fluxes of both atmospheric‐source and biological‐source nitrate to rivers simultaneously, making it unclear whether precipitation increases the relative contribution of atmospheric‐source nitrate in rivers. To gain a deeper insight into this issue, this study leveraged the significant precipitation gradient of the Yarlung Tsangpo River Basin, which spans the entire southern Tibetan Plateau, to explore the impact of precipitation on the relative contribution of atmospheric‐source nitrate (fatm) in rivers using the Δ17O–NO3− approach. The results showed that fatm can be as high as 20% particularly in areas with substantial precipitation, glacier and permanent snow coverage and lower nitrogen concentrations. fatm exhibited a strong positive correlation with precipitation in the Yarlung Tsangpo River Basin, although this relationship varied across individual rivers. Predictive models were developed to estimate the fatm in unsampled rivers, which could be valuable for watershed management and nitrogen budget calculations.